Correlation of Learning Motivation with Self Regulated Learning at SMA Negeri 1 Tasikmalaya City - Mustofa, Romy Faisal; Nabiila, Alyaa; Suharsono, Suharsono (International Journal for Educational and Vocational Studies, 2019)
Self-regulated learning is a constructive process that is active in setting learning goals. This ability should be possessed by every individual to become a successful learner. Another thing that students must have to be successful in the process and learning outcomes are learning motivation. This study aims to determine the correlation between learning motivation with self-regulated learning in grade X MIPA 9 SMA Negeri 1 Tasikmalaya City. This research was conducted in April 2019. The research method used was correlational with a population of all class X MIPA 9 students as many as 30 people. Samples were taken using a saturated sampling technique so that the entire population was sampled. The research instrument used in this study is the Motivated Strategies for Learning Questionnaire (MSLQ), which consists of 2 parts, namely motivational beliefs and self-regulated learning strategies. The data analysis technique used is the bivariate correlation regression test. Based on the results of the study, it can be concluded that there is a strong correlation (R = 0.761; R2 = 0.580) between learning motivation and self-regulated learning. The contribution of learning motivation to self-regulated learning is 58%.